Faring well in offshore wind power siting? Trust, engagement and process fairness in the United States. (April 2020) - Firestone, Jeremy; Hirt, Christine; Bidwell, David; Gardner, Meryl; Dwyer, Joseph
Abstract: Although visual effects may be the most defining characteristic of a wind project, implementing fair, transparent and just decision-making processes may be a significant determining factor in success. To shed light on this question, we undertook a study of perceptions of mainland coastal and island residents proximate to the Block Island project—the first offshore wind project in the United States. The study included a longitudinal survey of residents prior to and after turbine installation, and semi-structured interviews with residents and key stakeholders. We assessed the extent to which respondents were engaged in the planning process, opinions of transparency and fairness, and degree to which the planning process affected their opinion. Although interviewees who held a negative view of state government indicated that it did not cause them to oppose the project, trust in state government was the primary driver of perceptions of process fairness, which in turn was the primary driver of project support. We also found individuals to withhold final judgment of the process until the final outcome—project operation. Finally, fair process was seen as having benefits distinct from its effect on the outcome—that is, local residents valued the process itself.